Peregrinatio Interrupta: An Eclectic Success of a Failed Pilgrimage - Buttigieg, Noel (The international journal of religious tourism and pilgrimage, 2023)
This study explores the case study of two Quaker nuns, Ms Catherine Evans and Ms Sarah Cheevers. Their coincidental connection with the Mediterranean island of Malta caught the attention of several researchers, primarily interested in the micro history of the Quakers movement. Originally, Evans and Cheevers were entrusted to travel to Jerusalem, expecting to convert Christians at the epicentre of Christianity to Quakerism. After their ship called into the port of Malta en route to the Holy Land, their mission was interrupted due to their polarising and confrontational behaviour towards the Holy Office of the Roman Inquisition. Their intended short stay was turned into an incarcerated pilgrimage for about three and a half years. Based on the Quaker nuns’ criminal proceedings of the Inquisition Tribunal located in the Mdina Cathedral Archives of Malta and other published literature, various interpretations are explored regarding their missionary-pilgrimage experience in seventeenth-century Malta. The challenging situation experienced by these Quaker nuns during their detainment, their confined pilgrimage presents an intriguing opportunity to explore their experience as a spiritual and physical phenomenon, turning their mission into a missionary-pilgrimage experience. Considering the context within which this experience unfolds, and the complicated circumstances that dominated this situation, this study throws light on the historical context of how believers used temporal experiences, in this case the human body, as an attempt to navigate and communicate the spiritual world. Although the original missionary objectives could be easily regarded as an outright failure, it is here argued that the Quaker nuns continued their missionary purpose of preaching Quakerism. Conversely, their incarceration-turned-pilgrimage could be viewed as a resounding success, whereby the two nuns were able to reinforce their own understanding and beliefs in Quaker ideology while perpetuating their experiences among other Quaker communities.